2022
DOI: 10.1101/2022.08.09.503397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct roles of the two SEC scaffold proteins, AFF1 and AFF4, in regulating RNA Pol II transcription elongation

Abstract: The P-TEFb-containing super elongation complex (SEC) plays the essential role in transcriptional elongation control. The AF4/FMR2 family members AFF1 and AFF4 are the central scaffold proteins of SEC, associated with different human diseases. However, their specific roles in transcriptional control remain unclear. Here, we report that AFF1 and AFF4 show distinct genomic distribution patterns around TSS. AFF1 binds upstream of TSS, while AFF4 is enriched downstream of TSS. Pol II occupancies are reduced genome-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Furthermore, the depletion of AFF4 has been correlated with a deceleration in transcription elongation speed and premature termination of transcription. Conversely, insufficiency in AFF1 expedites transcription elongation and induces transcriptional readthrough 24 . These findings highlight the nuanced and precise regulation of Pol II pause release by the unique functions of AFF4 and AFF1, despite both serving as scaffolds for SEC.…”
Section: The Mechanism and Function Of Secmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the depletion of AFF4 has been correlated with a deceleration in transcription elongation speed and premature termination of transcription. Conversely, insufficiency in AFF1 expedites transcription elongation and induces transcriptional readthrough 24 . These findings highlight the nuanced and precise regulation of Pol II pause release by the unique functions of AFF4 and AFF1, despite both serving as scaffolds for SEC.…”
Section: The Mechanism and Function Of Secmentioning
confidence: 88%
“…Che et al. reported that AFF1 primarily localizes upstream of TSS, while AFF4 is positioned downstream 24 . Furthermore, the depletion of AFF4 has been correlated with a deceleration in transcription elongation speed and premature termination of transcription.…”
Section: The Mechanism and Function Of Secmentioning
confidence: 99%
See 1 more Smart Citation